Zircon Petrochronology and 40Ar/39Ar Thermochronology of the Adamello Intrusive Suite, N. Italy: Monitoring the Growth and Decay of an Incrementally Assembled Magmatic System. (20th February 2019) - Schaltegger, U; Nowak, A; Ulianov, A; Fisher, C M; Gerdes, A; Spikings, R; Whitehouse, M J; Bindeman, I; Hanchar, J M; Duff, J; Vervoort, J D; Sheldrake, T; et al.
Abstract: The Adamello intrusive suite is a composite batholith in Northern Italy, with an estimated 2000 km 3 volume, assembled incrementally over a time span of 10 to 12 million years. The history of crystallization has been studied in detail through laser ablation ICP-MS and SIMS U–Pb geochronology of zircon, which records prolonged crystallization of each of the different intrusive units at mid-crustal levels between 43·47 and 33·16 Ma. The magmas were episodically extracted from this storage area and ascended to the final intrusion level at ∼6 km paleo-depth. Each batch of melt cooled very rapidly down to the ambient temperature of 250°C, evidenced by distinct cooling paths recorded by amphibole, biotite and K-feldspar 40 Ar/ 39 Ar dates. The magma source area was moving from SW to NE with time, causing increasing thermal maturity in the mid-crustal reservoir. The resulting temporal trend of higher degrees of crustal assimiliation in the course of the evolution of the magmatic system can be traced through Hf and O isotopes in zircon. Rough estimates of magma emplacement rates ('magma flux') yield very low values in the range of 10 -4 km 3 /yr, typical of mid-to-upper crustal plutons and increase with time. Although we cannot discern a decrease of magma flux from our own data, we anticipate that a dramatic decrease of magma flux between 33 and 31 Ma along the northern contact lead to cessation of magma emplacement.